Utility and accuracy of perceptual voice and speech distinctions in the diagnosis of Parkinson's disease, PSP and MSA-P. (June 2017) - Miller, Nick; Nath, Uma; Noble, Emma; Burn, David
Aim: To determine if perceptual speech measures distinguish people with Parkinson's disease (PD), multiple system atrophy with predominant parkinsonism (MSA-P) and progressive supranuclear palsy (PSP).Methods: Speech–language therapists blind to patient characteristics employed clinical rating scales to evaluate speech/voice in 24 people with clinically diagnosed PD, 17 with PSP and 9 with MSA-P, matched for disease duration (mean 4.9 years, standard deviation 2.2).Results: No consistent intergroup differences appeared on specific speech/voice variables. People with PD were significantly less impaired on overall speech/voice severity. Analyses by severity suggested further investigation around laryngeal, resonance and fluency changes may characterize individual groups.Conclusion: MSA-P and PSP compared with PD were distinguished by severity of speech/voice deterioration, but individual speech/voice parameters failed to consistently differentiate groups.